Cervical Carcinoma in the European Union. Issue 3 (March 2015) - Altobelli, Emma; Lattanzi, Amedeo
<x xml:space="preserve">Abstract</x> Objective Cervical cancer (CC) is defined as a disease of disparity. This is due to marked differences in CC incidence and mortality between developed and developing countries. As a continent, Europe is no exception. This study examines the state of activation of CC screening in the European Union as of March 2014, reviews CC incidence and mortality data, and highlights the initiatives adopted to extend program coverage to nonresponders. Methods The present study is based on the most recent data available from PubMed-indexed journals, the Web sites of the health ministries of each member state, and the Web sites of national cancer observatories; failing these sources, information was sought in scientific journals published in the local language. Results In 2003, the European Council recommended that priority be given to organized screening program activation. Nonetheless, a number of European Union member states still lack population-based organized screening programs, and few have implemented programs directed at disadvantaged populations. Conclusions Several investigations have demonstrated that the women at higher CC risk are unscreened and underscreened ones. Since then, several member states have made significant efforts to set up effective prevention programs by adopting international quality standards and centralizing screening organization and result evaluation. Several developed countries and some new central-eastern European member states have poorly organized prevention programs that result in poor women's health. Diagnosis of CC is emotionally traumatic, but it is highly preventable. When CC is found early, it is highly treatable and associated with long survival and good quality of life.